The impact of temporal framing of breast cancer risk on perceptions of and motivations to engage with information about early diagnosis: Evidence from an online experiment - Sandro Tiziano Stoffel; Camilla Natale; Christian von Wagner (PLoS ONE, 2025)
This study investigates the application of Construal Level Theory (CLT) to grasp how individuals perceive and respond to breast cancer risk in both near and distant future scenarios. Employing a two-stage methodology, we initially conducted a preliminary survey with 201 women aged 40 to 50, evaluating their perceptions of various phrasings of breast cancer risk information, including ‘1 in x’, ‘x% of’, and ‘x-y% probability’. Subsequently, an online experiment involving 1052 women in the same age group explored the influence of temporal framing on perceived risk and intentions for breast self-checks. We selected the most understandable, imaginable, and motivational phrasing from the preliminary survey for the experiment. The participants were divided into two groups: near-future framing (N = 526) and distant-future framing of developing breast cancer (N = 526). Study 1 revealed that women found the ‘1 in x’ framing to be the easiest to understand, imagine, and most motivational. However, the subsequent experiment (Study 2) did not find any significant effects of temporal framing on women’s perceived risk of developing breast cancer, perceived importance of self-checks, intention to conduct self-checks, or interest in learning more about self-checks. Nonetheless, it was noteworthy that individuals exposed to near-future framing perceived their risk as closer in time compared to those presented with distant-future framing (OR = 1.42, 95% CI: 1.15-1.77 p = 0.001; aOR = 1.42, 95% CI: 1.14-1.76; p = 0.002). In conclusion, our study found that temporal distance of breast cancer risk doesn’t affect risk perception or information-seeking behaviour, suggesting a focus on clear, motivational risk communication rather than temporal framing alone.